CircRNA-Encoded Peptides or Proteins as New Players in Digestive System Neoplasms - Meng, Enqing; Deng, Jie; Jiang, Rongqi; Wu, Hao (Frontiers in Oncology, 2022)
Circular RNAs (circRNAs) were considered non-coding RNAs. Nowadays, a large number of studies have found that these RNAs contain open reading frames that can be translated in a cap-independent manner, such as internal ribosome entry site（IRES）and N6-methyladenosine（m6A）. The encoded peptides or proteins affect the occurrence and development of tumors by regulating the Yap-hippo and the Wnt-β/catenin signaling pathways, as well as the malignant progression of tumors through phosphorylation and ubiquitination of specific molecules. This review will summarize the regulation of circRNA translation and the functional roles and underlying mechanisms of circRNA-derived peptides or proteins in digestive tract tumors. Some circRNA-encoded peptides or proteins may be used as tumor biomarkers and prognostic factors for early screening and treatment of clinical gastrointestinal tumors.